Health : a right for all - the challenge of Haiti (PAHO Washington, D.C.US, 2006)
Shares some of the activities developed by PAHO/WHO in the last few years in Haiti. Informs about the achievements attained in the health sector resulting from collaborative efforts. Reaffirms that achieving "Health for All" is not a utopian ideal, but rather an attainable goal even for countries facing complex situations such as Haiti.
Keywords: HEALTH